Sosialisasi Pencegahan Bullying Di SMP Kristen Waikabubak Sumba Barat Berdasarkan Undang-Undang Nomor 35 Tahun 2014 - Jenny Ermalinda; Agnes Doortji Rema; Sigit Prabowo Sonbait (AMMA : Jurnal Pengabdian Masyarakat, 2024)
Education plays an important role in shaping the character and personality of the younger generation, including in the school environment. One of the social problems that often occurs in schools is bullying, which has a negative impact on the mental and physical well-being of the victim. Bullying can affect the mental health of the victim, causing anxiety, depression, and physical disorders, as well as disrupting the learning atmosphere. Waikabubak Christian Middle School, as an educational institution in West Sumba Regency, plays an important role in creating a safe and comfortable school environment. Therefore, socialization was carried out to prevent bullying, by involving students and teachers and educating them about the dangers of bullying, the importance of mutual respect, and children's rights protected by the Child Protection Law. The implementation of this socialization used an interactive approach such as seminars, group discussions, and ice-breaking games to increase student awareness. The results of the socialization showed that most students previously considered bullying to be normal, but after being given further understanding, they began to realize its negative impacts, both for victims and perpetrators. It is hoped that this activity can create a school environment that is free from violence and supports the optimal development of students.